POLICY ANALYSIS FOR HANDLING CRIMINAL OFFENSES IN THE FIELD OF CUSTOMS IN TERMS OF SMUGGLING OF SHARK FIN EXPORTED GOODS BY THE DIRECTORATE GENERAL OF CUSTOMS AND EXCISE - Brian William Leimena (Universitas Labuhanbatu, 2024)
The existence of the Customs Law, has regulated provisions regarding entering goods into the customs area including criminal sanctions attached to customs crimes, but cannot discourage smuggling actors (entering goods into the customs area illegally). When viewed from a legal perspective, perpetrators of smuggling can carry out various types of smuggling and their modus operandi is from smuggling which can fall into the category of material or immaterial losses. Meanwhile, recently the author has found that there are cases of shark fin smuggling which are being handled by the Tanjung Perak Medium Type Customs and Excise Supervision and Service Office. The research method uses a Normative Juridical approach, in nature, this research is categorized as descriptive research without intending to test hypotheses or theories, but is an activity of analyzing and classifying or systematizing legal materials. The crime of smuggling in Indonesia is influenced by several factors that are causally related. The factors that encourage the crime of smuggling are: Presidential Instruction Regulation (INPRES) Number 4 of 1985 concerning Policy on Smooth Flow of Goods to Support Economic Activities. Communities in efforts to combat smuggling crimes often feel a lack of participation. Exporters are lazy to submit them on the grounds that the permit levels are very long. Law Enforcement in the Criminal Act of Smuggling in the export sector is regulated by regulation in the criminal provisions of the Customs Law Article 102A stipulates an act that is considered as smuggling or that can be categorized as a criminal act of smuggling if it fulfills the following elements, namely: There is an act against the law. Transporting export goods that are not listed in the manifest. Loading or transporting export goods from inside the customs area to outside the customs area or other places without permission from the head of the customs office; Unloading export goods in the customs area without permission from the head of the customs office; or transporting exported goods without being protected by valid documents. Keywords: Export; Customs; Smuggling; Shark fin; Criminal act